Analisis Daya Saing dan Faktor yang Mempengaruhi Ekspor Teh di Pasar Internasional - Septino Adi Surya (Universitas Muhammadiyah Surakarta, 2023)
Competitiveness is a key in a cross-country economic order. The level of competitiveness is calculated based on commodity exports in a country. Tea is one of Indonesia's export products. This study aims to analyze competitiveness and the influence of production, international prices, land area, imports and exchange rates on the competitiveness of Indonesian tea. The method used is Revealed Comparative Advantage (RCA) to analyze the competitiveness of Indonesian teaexports in the international market and the multiple linear regression method to analyze the factors that influence the competitiveness of Indonesian tea exports. The data used in this study are time series secondary data from 2001 to 2022. The results of the study show that international production and prices do not have a significant effect on the competitiveness of Indonesian tea exports. Land area has a significant positive effect on the competitiveness of Indonesian tea exports. Imports and exchange rates have a significant negative effect on the competitiveness of Indonesian tea exports.